Knowledge management perception: An exploratory study of a payphone company in Malaysia - Omar, Mohd Misron; Md Akhir, Romiza; Shaikh Awadz, Azlina; Abdul Hamid, Noor Raihan (2010)
This paper will discuss the survey that was carried out in Malaysia’s biggest payphone company.Payphone service is considered a sunset business.However, it is part of the social responsible corporate entity that supports the public payphones project embarked by the government under the Universal Service Provision (USP) fund at various rural and remote locations throughout Malaysia.The main objective of this research is to assess employees’ perception towards KM initiatives in the payphone organization.Data were collected through questionnaires survey with technical support staff, engineers and managers. Descriptive analyses were conducted which include respondent’s profiles, types of challenges faced by the organisation and employees’ perception of KM practices.One of the findings indicated that people-to-people relationship is important in implementing effective KM in the organization.